Magnetic pulsed processing of metals for advanced technologies of modernity – a brief review - Batygin, Yu.V.; Chaplygin, E.A.; Sabokar, O.S. (Електротехніка і електромеханіка, 2016)
The aim of the article is dedicated to the brief review of the main achievements of the advanced technologies with usage of the energy of the pulsed magnetic fields. Originality. The new suggestions are represented. They are based on the results of development of the new scientific direction in area of the magnetic pulsed processing of thin-walled sheet metals when a penetration of the acting fields is quite significant. The known traditional approaches based on the skin-effect in electrodynamics and were successfully implemented. Methodology of the analysis consist of careful theoretical and practical experiments review and its future development. Results of the research based on the existing experimental approbation were presented visually with the description followed The known approaches to solution actual production problems based on the skin-effect in electrodynamics are described. Practical value. The first of practical propositions is related to stamping of the drawing the printed circuit boards on the cooper foil with thickness about ~50 mkm. This operation is realizing by the forces of magnetic pressure directly without any supplements introduction. The second consists in usage the magnetic pulsed attraction for external removing the dents in the car body. This operation does not demand disassembling of elemental base and allows preserving the paint of coverings. Both of these technologies could to minimize the working time, to decries the volume of the waste products and to make the manufacturing existed much cheaper.